The effect of telerehabilitation on balance in stroke patients: is it more effective than the traditional rehabilitation model? A meta-analysis of randomized controlled trials published during the COVID-19 pandemic - Su, Zhaoyin; Guo, Zhenxia; Wang, Weitao; Liu, Yao; Liu, Yatao; Chen, Wanqiang; Zheng, Maohua; Michael, Nerich; Lu, Shuai; Wang, Weining; Xiao, Handan (Frontiers in Neurology, 2023)
Abstract Objective In 2019, the outbreak of COVID-19 started in Wuhan. So far, most countries have opted to coexist with the virus. However, patients, especially those who have suffered a stroke should avoid being infected with any disease as much as possible for the reason that any infectious disease can lead to adverse events in them. This meta-analysis aims to investigate the effects of telerehabilitation on the balance ability of stroke patients, compare the efficacy between conventional rehabilitation and telerehabilitation, and to provide recommendations for rehabilitation programs against the backdrop of the global pandemic. Methods We searched Pubmed, Embase, Web of science, and The Cochrane Library from January 1st, 2020 to December 31st, 2022 for randomized controlled trials published in English, which evaluated the improvement of balance function in stroke patients after telerehabilitation and compared the differences between telerehabilitation (TR) and conventional rehabilitation (CR). The studies were imported into endnote and excel and screened in two stages by 4 reviewers. Data on relevant outcomes were extracted and analyzed using STATA17.0 software. Results We included 9 studies in the system evaluation, all of which were included in the pooled analysis. All outcomes in the experimental and control groups improved over time. People who received the telerehabilitation intervention had a significant improvement in the Berg Balance Scale and Fugl-Meyer Assessment. The Timed up and go test and Tinetti performance-oriented mobility assessment-Balance were better in the control group than in the experimental group. There were no significant differences in other outcomes between the two groups. Conclusion Studies under changes in medical conditions during the COVID-19 pandemic can also demonstrate that telerehabilitation for stroke patients achieves similar effects as the conventional rehabilitation mode. Because of the different equipment and intervention programs of telerehabilitation, the curative effect of telerehabilitation on the static balance and reactive balance of stroke patients may be different. Further studies are needed for investigating the difference in efficacy between varied devices and rehabilitation programs of telerehabilitation. Meanwhile, such research needs more literature and larger sample size to support more definitive findings based on the backdrop of the COVID-19 pandemic.